PENGARUH FAKTOR SOSIAL DAN NILAI PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPEDA MOTOR YAMAHA DI KABUPATEN DEMAK - Dyah Kusumawati (JAB (Jurnal Akuntansi & Bisnis), 2019)
ABSTRACTThis study aims to analyze the influence of social factors and customer value on purchasing decisions for Yamaha motorcycle products. The population is everyone who has ever bought a Yamaha motorcycle, with a sample of 75 people and uses the Roscoe formula. The sampling technique using convenience sampling. The results of testing the hypothesis using the two-stage regression method showed that the value of t arithmetic social factors on purchasing decisions 0.072 <t table = 1.993 with a significance of 0.943> α = 0.05 (significant), then hypothesis 1 (H1) was not proven and had a positive effect. This can be interpreted that the higher the social factors, the purchasing decision process may not necessarily be fast. The value of t calculate the value of customers to the purchase decision 0.843 <t table = 1.993 with a significance of 0.402> α = 0.05 (significant), then hypothesis 2 (H2) is not proven and has a positive effect. This can be interpreted that the higher the customer value is not necessarily the purchasing decision process happens quickly.. Keywords: Social Factors, Customer Value, Purchasing Decisions.